2018
DOI: 10.1038/s41467-017-02682-y
|View full text |Cite
|
Sign up to set email alerts
|

Human caspase-4 detects tetra-acylated LPS and cytosolic Francisella and functions differently from murine caspase-11

Abstract: Caspase-4/5 in humans and caspase-11 in mice bind hexa-acylated lipid A, the lipid moeity of lipopolysaccharide (LPS), to induce the activation of non-canonical inflammasome. Pathogens such as Francisella novicida express an under-acylated lipid A and escape caspase-11 recognition in mice. Here, we show that caspase-4 drives inflammasome responses to F. novicida infection in human macrophages. Caspase-4 triggers F. novicida-mediated, gasdermin D-dependent pyroptosis and activates the NLRP3 inflammasome. Inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
176
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(189 citation statements)
references
References 64 publications
12
176
1
Order By: Relevance
“…To demonstrate that the difference in PKC inhibitor responses in monocytes from FMF patients and HD was specifically due to MEFV mutation, we generated U937 cells expressing either WT MEFV or p.M694V MEFV . U937 were invalidated for the MEFV gene (Lagrange et al , ) to avoid any possible confounding factor and complemented with either 3xFLAG‐WT (Lagrange et al , ) or 3xFLAG‐p.M694V MEFV under the control of a doxycycline‐inducible promoter (Fig EV2A). The Pyrin immunoblot pattern obtained upon doxycycline addition was similar to the pattern previously described in PBMCs (Chae et al , ) with a major cleavage band around 50 kDa (Fig EV2B).…”
Section: Resultsmentioning
confidence: 99%
“…To demonstrate that the difference in PKC inhibitor responses in monocytes from FMF patients and HD was specifically due to MEFV mutation, we generated U937 cells expressing either WT MEFV or p.M694V MEFV . U937 were invalidated for the MEFV gene (Lagrange et al , ) to avoid any possible confounding factor and complemented with either 3xFLAG‐WT (Lagrange et al , ) or 3xFLAG‐p.M694V MEFV under the control of a doxycycline‐inducible promoter (Fig EV2A). The Pyrin immunoblot pattern obtained upon doxycycline addition was similar to the pattern previously described in PBMCs (Chae et al , ) with a major cleavage band around 50 kDa (Fig EV2B).…”
Section: Resultsmentioning
confidence: 99%
“…On the following day, the mice were immunized with the anti-TLR4 mAb or LPS at the indicated doses with (a) 100 lg or (b) 10 lg ovalbumin (OVA). 52,53 In contrast, the anti-TLR4 agonistic mAb activates TLR4, but not caspases, because of its high specificity and inability to penetrate the cell membrane. Representative histograms and dot plots are shown.…”
Section: Discussionmentioning
confidence: 99%
“…(a) Two or (b) three days after immunization, spleen cells were subjected to FACS analysis to evaluate the proliferation of transferred OT-I and OT-II T-cells. 36,37 The latter step, which is stimulated by non-canonical inflammasomes, 52,53 represents an obvious difference in the point of action between LPS and the anti-TLR4 mAb. The absolute numbers of (a) Ly5Á1 + CD8 + OT-I and (B) Ly5Á1 + CD4 + OT-II T-cells in the spleen, and the percentages of (a) CFSE low Ly5Á1 + CD8 + OT-I and (B) Ly5Á1 + CD4 + OT-I) T-cells are shown as means AE SEMs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data demonstrated that both caspase‐11 and its human homologues caspase‐4/5 bound hexa‐acylated lipid A, the lipid portion of LPS. Remarkably, the under‐acylated (tetra‐acylated) lipid A of the Gram‐negative bacterium Francisella novicida escaped caspase‐11 recognition in mice but was sensed by caspase‐4 in humans . Thus, caspase‐4 and caspase‐11 display distinct specificity for LPS.…”
Section: Caspase 11: the Noncanonical Inflammasome Receptormentioning
confidence: 99%
“…In fact, CARD domains of caspase‐11 and caspase‐4 shares 51% identity, which may explain the broader sensitivity of caspase‐4 in sensing LPS compared to caspase‐11. In addition, it was demonstrated that GBP2 promotes efficient sensing of under‐acylated LPS by caspase‐4, although GBP2 was dispensable for hexa‐acylated LPS recognition . In this case, GBP2 might act as human‐specific cofactor assisting under‐acylated LPS detection by caspase‐4 .…”
Section: Caspase 11: the Noncanonical Inflammasome Receptormentioning
confidence: 99%